Climate Obstruction in the European Union: Business Coalitions and the Technocracy of Delay - Dieter Plehwe; Moritz Neujeffski; Tobias Haas (Climate Obstruction across Europe, 2024)
The European Union has gained increasing influence in setting climate policy. Its power to determine the orientation of the integrated body and in negotiation and decision-making gives the European Union a privileged role in the climate policies of individual member states—and these processes are, accordingly, contested. At the EU level, efforts to obstruct ambitious action aim not to deny climate change but to reduce the ambition of policy initiatives and make them more market friendly. To capture the opposition, the chapter evaluates texts from key EU associations such as BusinessEurope as well as the output of conservative and neoliberal European think tanks and networks such as the Centre for European Policy. It also examines the influence of fossil fuel and `green' lobby groups and analyses the extent to which actors have been able to implement their climate obstruction activities through direct contacts within the European Commission.
Keywords: 300; carbon leakage; climate change; climate obstruction; emissions trading; European Union; green deal; green taxonomy; single market; technology neutrality; think tank